ANALISIS FAKTOR AKSES PELAYANAN KESEHATAN DENGAN JUMLAH KEMATIAN BAYI DI JAWA TIMUR - Vema Aisya Rahma; Soenarnatalina Melaniani (Poltekkes Kemenkes Surabaya, 2016)
Infant Mortality Rate (IMR) is one of the indicators in the MDGs. Data show that IMR in East Java in 2014 has not been able to achieve the MDGs. AKB higher indicates the number of infant deaths in an area becomes high. The number of infant deaths classified as discrete data. Analysis of factors that can be used to discrete data is negative binomial regression. Negative binomial regression has advantages such as the absence of assumptions equidispersi the poisson regression. The research aims to analyze the access to health services (the ratio of public health centers and the ratio of midwives) which may affect on the number of infant deaths in East Java. This is non reactive research that used published secondary data. Results showed that access to health services (the ratio of public health centers and the ratio of midwives) can affect the number of infant deaths. Infant mortality decreased when the ratio of public health centers and the ratio of midwives increases. Keyword : AKB, the number of infant deaths, binomial negative regression, the acsess to health service